Does the disclosure of medical insurance information affect patients’ willingness to adopt the diagnosis related groups system - Shi, Zhenni; Zhang, Qilin; Wang, Xiaofeng (Frontiers in Public Health, 2023)
Medical insurance information disclosure is not only a direct way for the public to understand and master social insurance information and resource use benefits, but also an important way for the public to participate in medical service governance and supervision. Some studies have shown that information disclosure has a significant impact on reducing risk perception caused by information asymmetry. This paper focuses on the influence mechanism of patients' attitudes during the implementation of DRG payment system. Taking the medical insurance information disclosure under the governance perspective as the research object, we analyze the willingness of medical insurance information disclosure to patients to adopt DRG payment system by means of questionnaires, and at the same time, we deeply explore the impact mechanism of medical insurance information disclosure on patients' attitudes. The research has found that risk perception and trust perception has played a key role.